2022
DOI: 10.1183/13993003.03200-2021
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk in severe alpha-1-antitrypsin deficiency

Abstract: BackgroundSevere alpha-1-antitrypsin deficiency (AATD), phenotype PiZZ, is a risk factor for pulmonary emphysema and liver disease, but its effect on cancer risk is unknown. Our aim was to evaluate the risk and the risk factors for incident cancer in PiZZ individuals compared with the general population with known smoking habits.MethodsA longitudinal study of PiZZ individuals (n=1595) from the Swedish National AATD Register, and controls (n=5999) from Swedish population-based cohorts. Data on cancer and mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Another major caveat are the lacking data about the development of hepatocellular carcinoma (HCC). While the absolute risk seems to be 20-50x elevated in Pi*ZZ subjects [45,54], the current data suggest that it develops primarily in subjects with advanced liver fibrosis [55],…”
Section: Accepted Manuscriptmentioning
confidence: 45%
See 1 more Smart Citation
“…Another major caveat are the lacking data about the development of hepatocellular carcinoma (HCC). While the absolute risk seems to be 20-50x elevated in Pi*ZZ subjects [45,54], the current data suggest that it develops primarily in subjects with advanced liver fibrosis [55],…”
Section: Accepted Manuscriptmentioning
confidence: 45%
“…Another major caveat is the lacking data about the development of hepatocellular carcinoma (HCC). While the absolute risk seems to be 20 to 50 times elevated in Pi à ZZ subjects, 45,54 the current data suggest that it develops primarily in subjects with advanced liver fibrosis, 55 who should receive ultrasound-/imagingbased HCC screening every 6 months. Given that liver cirrhosis constitutes an increased risk for HCC, we advocate for HCC screening for all AATD patients with cirrhosis, irrespectively of their genotype.…”
Section: Liver Disease In Adulthoodmentioning
confidence: 68%
“…This leads us to believe that the problem may stem from AAT activity. Its dysfunction would cause an imbalance between protease-antiprotease, not in quantity but rather functionality, where despite normal or even elevated AAT levels, said protein has little or no anti-elastase activity ( 4 , 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data clearly indicated that miR-425-5p expression was significantly decreased in AATD individuals. Given that AATD individuals may have an increased risk of developing hepatocellular carcinoma (86) decreased levels of plasma EV-associated miR-425-5p may suggest a defense mechanism to prevent cancer in this patient's population.…”
Section: Discussionmentioning
confidence: 99%